2018
DOI: 10.1111/jpn.12868
|View full text |Cite
|
Sign up to set email alerts
|

Effects of low phosphorus supply on the availability of calcium and phosphorus, and musculoskeletal development of growing dogs of two different breeds

Abstract: To investigate the impact of a selective reduction in dietary phosphorus (P) supply on healthy growing dogs, a total of 23 Beagles and 30 Foxhound crossbreds (FBI) were used in a feeding trial between 6 and 24 weeks of age. Sixteen Beagles and 19 FBI were fed with selectively reduced P concentrations (low phosphorus, LP). The remaining puppies received a completely balanced control diet (CON). With these diets, the P supply in the Beagles at the age of 12 weeks added up to 2.5 ± 0.6 (LP) and 9.8 ± 1.4 g P/kg D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 29 publications
(56 reference statements)
1
23
0
1
Order By: Relevance
“…In puppies the negative impact of an undersupply with P onto the musculoskeletal system has been described. Affected puppies showed a loss of muscle strength, deviation of the limb axis and hyper exion of joints, indicating the demand of P also for the connective tissue [21]. Several studies have shown that P-reduced feeding can cause degenerative but also other pathological skeleton alterations.…”
Section: Discussionmentioning
confidence: 99%
“…In puppies the negative impact of an undersupply with P onto the musculoskeletal system has been described. Affected puppies showed a loss of muscle strength, deviation of the limb axis and hyper exion of joints, indicating the demand of P also for the connective tissue [21]. Several studies have shown that P-reduced feeding can cause degenerative but also other pathological skeleton alterations.…”
Section: Discussionmentioning
confidence: 99%
“…In puppies, a negative impact of P de ciency on the musculoskeletal system has been described. Affected puppies showed a loss of muscular activity, deviation of the limb axis and hyper exion of joints, indicating the demand for P also for the connective tissue [45]. Several studies have shown that dietary P de ciency can cause degenerative but also other pathologic skeletal alterations.…”
Section: Discussionmentioning
confidence: 99%
“…Details regarding the components, composition of the diets and the feeding regime are provided in Kiefer‐Hecker et al. ().…”
Section: Animals Materials and Methodsmentioning
confidence: 99%
“…It has been previously documented in canine nutrition that P excess (Anonymous, ; Gagné, Wakshlag, Center, Rutzke, & Glahn, ) as well as P depletion (Anonymous ; Fritz, Rosenberg, Bensinger, & Kienzle, ; McMillan, Griffon, Marks, & Mauldin, ) occurs. Negative effects on the skeletal and overall health due to P depletion were demonstrated in various species (dog: Lipschütz, ; Jenkins & Phillips, ; Fuller, Carter, Barcenas, & Knochel, ; Kiefer‐Hecker, Kienzle, & Dobenecker, ; cat: Kienzle, Thielen, & Pessinger, ; man: Lotz, Zisman, & Bartter, ; Kreusser, Ritz, Boland, & Brachmann, ). However, data about the relationship between P restriction and its projected impact on certain serum values in growing dogs is sparse.…”
Section: Introductionmentioning
confidence: 99%